Technological and market innovation : - Nystrom, Harry (Wiley, 1990)
The ideas and empirical results presented are the result of ongoing research on a wide range of strategic management issues. Illustrated by case studies taken from Scandinavian companies in a variety of industries, it indicates the implications of the research results and discusses directions for future research, covering such important topics as how to manage technological innovation and change, image marketing, product development, and corporate strategy.